A long way from home - McKay, Claude, 1890-1948 (MELA (Multi-ethnic Literatures of the Americas), 2007)
Claude McKay (1889?1948) was one of the most prolific and sophisticated African American writers of the early twentieth century. A Jamaican-born author of poetry, short stories, novels, and nonfiction, McKay has often been associated with the?New Negro? or Harlem Renaissance, a movement of African American art, culture, and intellectualism between World War I and the Great Depression. But his relationship to the movement was complex. Literally absent from Harlem during that period, he devoted most of his time to traveling through Europe, Russia, and Africa during the 1920s and 1930s. His acti.